2021
DOI: 10.3390/genes12050664
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Variants Located in the MIR196A2, MIR146A, and MIR423 with Type-2 Diabetes Mellitus in Pakistani Population

Abstract: MicroRNAs (miRNAs) are small non-coding RNA molecules that control the post-transcriptional gene expression. They play a pivotal role in the regulation of important physiological processes. Variations in miRNA genes coding for mature miRNA sequences have been implicated in several diseases. However, the association of variants in miRNAs genes with Type 2 Diabetes Mellitus (T2DM) in the Pakistani population is rarely reported. Therefore, the current study was designed to investigate the association of rs1161491… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…The results on MIRNA SNPs showed that the CT genotype and the T allele of MIR-196A-2 rs11614913 were associated with T2DM. This result is in agreement with a recent study that reported MIR-196A-2 rs11614913 to be associated with T2DM in a Pakistani population ( 42 ). The MIR-196A-2 rs11614913 C>T SNP has been reported to influence the expression of mature mRNAs by binding with target mRNAs ( 25 , 43 ), and the T allele is associated with reduced mature miR-196a-2 levels ( 44 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results on MIRNA SNPs showed that the CT genotype and the T allele of MIR-196A-2 rs11614913 were associated with T2DM. This result is in agreement with a recent study that reported MIR-196A-2 rs11614913 to be associated with T2DM in a Pakistani population ( 42 ). The MIR-196A-2 rs11614913 C>T SNP has been reported to influence the expression of mature mRNAs by binding with target mRNAs ( 25 , 43 ), and the T allele is associated with reduced mature miR-196a-2 levels ( 44 ).…”
Section: Discussionsupporting
confidence: 93%
“…They further reported that the overexpression of mir-423-5p enhanced gluconeogenesis, increased blood glucose levels and obesity in healthy mice through the suppression of the hepatic FAM3A/ATP/Akt pathway (30). However, the result is in disagreement with a study that reported no association of rs6505162 with the induction of T2dM in the Pakistani population (42). This dissimilarity of findings is probably due to different subject ethnicity and sample size and requires further validation.…”
Section: Discussionmentioning
confidence: 94%
“…Three papers in this section take an interesting approach of examining variants in miRNAs that may be associated with two diseases-type 2 diabetes mellitus (T2D), and coronary artery disease. Khan and colleagues examined previously characterized single nucleotides variants in miR-196-a2, miR-146a, and miR-423 with their association in T2D patients from the Pakistani population [29]. By using the tetra-primer amplification refractory mutation system "ARMS"-based PCR, variants in two of these miRNAs were shown to have a strong association with T2D in this population.…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…Haq and colleagues used 223 patients, and 150 controls to find that variants in miR-27A and miR-196-a2 (rs895819, and rs11614913, respectively) showed co-dominant or dominant association with coronary artery disease [31]. Of note, miR-196-a2 was described by the previous study on dia-betes [29], and recently also as a marker of colorectal cancer [32], all noting the correlation with rs11614913. Novak and colleagues took a slightly different approach by examining a variant within the putative binding site for miR-31/-584 in the angiotensinogen (AGT) gene, and found that the CC genotype for rs7079 in the 3 untranslated region of the AGT gene was significantly correlated with earlier onset of clinical referral in patients with coronary artery disease, and presentation with reduced coronary artery diameter (restenosis), after angioplasty [33].…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%